Clinical parameters and emerging biomarkers of partial remission in pediatric type 1 diabetes: a systematic review - Dikranian, Camille; Hadara, Oumayma; Lysy, Philippe A. (Frontiers in Endocrinology, 2026)
BackgroundIn type 1 diabetes (T1D), partial remission (PR) is a pivotal phase with preserved β-cell function, better glycemic stability, and reduced disease burden, and is as such a potential target for disease-modifying interventions. Identifying robust biomarkers of PR is critical for designing targeted therapies. This systematic review synthesizes current evidence from observational studies of biomarkers associated with PR in pediatric T1D.MethodsWe searched the literature in PubMed, Scopus, and Embase (2009–2025), using strategies based on PICOS criteria. Investigated biomarkers covered multiple domains: anthropometric and clinical factors, continuous glucose monitoring metrics, HLA genotyping, immune cell and cytokine profiles, hormones, proteomics, and microRNAs. Eligible studies included observational cohorts of children and adolescents with newly diagnosed T1D. PR was defined as IDAA1c ≤9, HbA1c <7% with insulin requirement <0.5 IU/kg BW/day, or stimulated C-peptide ≥ 300pmol/L. Studies were selected according to PRISMA guidelines, and risk of bias was appraised using the Joanna Briggs Institute checklist.ResultsOf 353 records, 39 studies including 9,368 patients met the inclusion criteria. Study populations ranged from 16 to 3,657 participants, with mean age of disease onset ranging from 7.0 to 13.8 years. Most studies (n=32) defined PR using IDAA1c. Routine clinical parameters and CGM-derived indices consistently distinguished remitters from non-remitters. Biological markers like immune signatures or proteomic profiles provided mechanistic insights into PR pathways. The methodological quality was moderate to high, though control of confounders and follow-up were incomplete.ConclusionStandard-of-care biomarkers appear sufficient to identify PR and monitor its impact on glycemic outcomes. Emerging biological markers offer promising insights into the underlying mechanisms of PR. Well-powered studies are needed to clarify PR determinants and their therapeutic potential.